Partisipasi Politik dalam Pemerintahan Non Muslim Perspektif Yusuf Qardawi - Sugianto Sugianto; Rahmat Hidayat; Agus Sujarwo (IAIN Batusangkar, 2021)
This study aims to reveal the thoughts of Yususf Qordawi about Muslim political participation in non-Muslim governments. Data obtained from the main source in the form of the book ghoiru Muslim fi al-mujtama 'al Islami (non-Muslim minority in the Islamic society). Then the data were analyzed using the content analysis method. The results showed that the existence of a Muslim must be carried out within the framework of the state and society life order as an implementation of obedience to the leader. This thought is based on the interpretation of fundamental Islamic values in the sentence rahmatan lil 'alamin, in every case it must be placed in a balanced place and in accordance with the rules or laws that apply in the region. So Muslim participation in non-Muslim governments is allowed.